ESTRO ACROP guideline for target volume delineation of skull base tumors. (March 2021) - Combs, Stephanie E.; Baumert, Brigitta G.; Bendszus, Martin; Bozzao, Alessandro; Brada, Michael; Fariselli, Laura; Fiorentino, Alba; Ganswindt, Ute; Grosu, Anca L.; Lagerwaard, Frank L; Niyazi, Maximilian; Nyholm, Tufve; et al.
Highlights: This guideline aims to improve target volume delineation for skull base tumors. Organs of risk are defined and dose constraints for brain structures are given. MRI with high three-dimensional spatial accuracy improves target delineation. Target delineation and imaging issues for different skull base tumors are given. Abstract: Background and purpose: For skull base tumors, target definition is the key to safe high-dose treatments because surrounding normal tissues are very sensitive to radiation. In the present work we established a joint ESTRO ACROP guideline for the target volume definition of skull base tumors. Material and methods: A comprehensive literature search was conducted in PubMed using various combinations of the following medical subjects headings (MeSH) and free-text words: "radiation therapy" or "stereotactic radiosurgery" or "proton therapy" or "particle beam therapy" and "skull base neoplasms" "pituitary neoplasms", "meningioma", "craniopharyngioma", "chordoma", "chondrosarcoma", "acoustic neuroma/vestibular schwannoma", "organs at risk", "gross tumor volume", "clinical tumor volume", "planning tumor volume", "target volume", "target delineation", "dose constraints". The ACROP committee identified sixteen European experts in close interaction with the ESTRO clinical committee who analyzed and discussed the body of evidence concerning target delineation. Results: All experts agree that magnetic resonance (MR) images with high three-dimensional spatial accuracy and tissue-contrast definition, both T2-weighted and volumetric T1-weighted sequences, are required to improve target delineation. In detail, several key issues were identified and discussed: i) radiation techniques and immobilization, ii) imaging techniques and target delineation, and iii) technical aspects of radiation treatments including planning techniques and dose-fractionation schedules. Specific target delineation issues with regard to different skull base tumors, including pituitary adenomas, meningiomas, craniopharyngiomas, acoustic neuromas, chordomas and chondrosarcomas are presented. Conclusions: This ESTRO ACROP guideline achieved detailed recommendations on target volume definition for skull base tumors, as well as comprehensive advice about imaging modalities and radiation techniques.